Familial breast cancer and DNA repair genes: Insights into known and novel susceptibility genes from the GENESIS study, and implications for multigene panel testing. Issue 8 (13th November 2018) - Girard, Elodie; Eon‐Marchais, Séverine; Olaso, Robert; Renault, Anne‐Laure; Damiola, Francesca; Dondon, Marie‐Gabrielle; Barjhoux, Laure; Goidin, Didier; Meyer, Vincent; Le Gal, Dorothée; Beauvallet, Juana; Mebirouk, Noura; et al.
Abstract : Pathogenic variants in BRCA1 and BRCA2 only explain the underlying genetic cause of about 10% of hereditary breast and ovarian cancer families. Because of cost‐effectiveness, multigene panel testing is often performed even if the clinical utility of testing most of the genes remains questionable. The purpose of our study was to assess the contribution of rare, deleterious‐predicted variants in DNA repair genes in familial breast cancer (BC) in a well‐characterized and homogeneous population. We analyzed 113 DNA repair genes selected from either an exome sequencing or a candidate gene approach in the GENESIS study, which includes familial BC cases with no BRCA1 or BRCA2 mutation and having a sister with BC ( N = 1, 207), and general population controls ( N = 1, 199). Sequencing data were filtered for rare loss‐of‐function variants (LoF) and likely deleterious missense variants (MV). We confirmed associations between LoF and MV in PALB2, ATM and CHEK2 and BC occurrence. We also identified for the first time associations between FANCI, MAST1, POLH and RTEL1 and BC susceptibility. Unlike other associated genes, carriers of an ATM LoF had a significantly higher risk of developing BC than carriers of an ATM MV (ORLoF = 17.4 vs. ORMV = 1.6; p Het = 0.002). Hence, our approach allowed us to specify BC relative risks associated with deleterious‐predicted variants in PALB2, ATM and CHEK2 and to add MAST1, POLH, RTEL1 and FANCI to the list of DNA repair genes possibly involved in BC susceptibility. We also highlight that different types of variants within the same gene can lead to different risk estimates. Abstract : What's new? Pathogenic variants in BRCA1 and BRCA2 only explain the genetic cause of about 10% of hereditary breast and ovarian cancer families, and the clinical usefulness of testing other genes following the recent introduction of cost‐effective multigene panel sequencing in diagnostics laboratories remains questionable. This large case‐control study describes genetic variation in 113 DNA repair genes and specifies breast cancer relative risks associated with rare deleterious‐predicted variants in PALB2, ATM, and CHEK2. Importantly, different types of variants within the same gene can lead to different risk estimates. The results may help improve risk prediction models and define gene‐specific consensus management guidelines.